Identificação do nível de importância dos fatores críticos da gestão pela qualidade total nos resultados da qualidade do produto por meio da regressão linear múltipla - Araújo, Cledinaldo Castro (2012)
One of the major requirements of companies today is to establish a system that allows continuous improvement of products, increase productivity and reduce costs in order to keep them competitive in the global market. These goals can be achieved, for example, by Total Quality Management (TQM). An important point to be investigated with this approach is the contribution that critical success factors have in the quality results and in its implementation. In this context, the objective of this work is to apply a Multiple Linear Regression Model assessment in the importance level of TQM critical factors in manufacturing of medium and large based in the state of Ceará. The database comes from studies by Alexander (1999), Bosi (2010), Oliveira (2010) and Roberts (2010), meaning that this work is a secondary search. The research methodology for data collection, applied by these authors, was based on the achievement of quantitative research covering this universe on two occasions (1999 and 2010), by a structured questionnaire using Likert scale in five categories. At first, the research conducted by Alexander (1999) covered the universe of 75 companies, Radiograph stage of TQM practices in this industry, a comparative analysis with the practices followed in developed regions, some interventions proposed in an attempt to assist the implementation of TQM in manufacturing industries in the state of Ceará, the following works, whose data were collected by Bosi (2010), Oliveira (2010) and Rodrigues (2010), covered the universe of 91 companies. The questionnaires in 2010 were similar to those used in 1999, but were inserted questions about Environmental Management, Security Management and Ethics and Social Responsibility. Using the method of stepwise variable selection, we selected the critical success factors of TQM with the highest impact on quality results, whose regression coefficients correspond to their weights. Among other results, this study reveals that the factors changed significantly from 1999 to 2010 as well as their levels of importance. In 1999, only quality measurement and metrology are listed as relevant to quality results by multiple linear regression models. In 2010, only customer focuses, supplier partnership, measurements of quality and safety management were listed as relevant. Regarding to the use of quality programs, the number of companies using TQM grew 50% in 2010, and the number of companies using ISO 9000 grew 156%, which points to an important concern for companies’ use of quality programs.